Involution or Evolution? Conceptualizing the Changes in Farming System of Eastern Nepal - Chapagain, Prem Sagar (Himalayan Review, 2009)
The traditional farming system of growing cereal crops and livestock for the purpose of subsistence has gradually been replaced by the cash crops. Farmers, particularly after 1980, have started cultivating cash crops such as cardamom, ginger, broom-grass, orange and dairy cow for commercial purposes. Consequently, previously unused and marginal lands are now covered by these high value cash crops. These changes in farming system are neither just an intensifi cation nor they can be understood as agricultural involution. These changes in crops and cropping pattern have changed the agricultural landscape and environment resulting to agricultural evolution. Key words: Farming system, intensification, subsistence, stagnation, involution, cash The Himalayan Review Vol. XXXVII, 2006 Page: 1-17